Genomic Comparison of P-Type ATPase Ion Pumps in Arabidopsis and Rice - Baxter, Ivan (The American Society for Plant Biologists, 2003)
Members of the P-type ATPase ion pump superfamily are found in all three branches of life. Forty-six P-type ATPase genes were identified in Arabidopsis, the largest number yet identified in any organism. The recent completion of two draft sequences of the rice (Oryza sativa) genome allows for comparison of the full complement of P-type ATPases in two different plant species. Here, we identify a similar number (43) in rice, despite the rice genome being more than three times the size of Arabidopsis. The similarly large families suggest that both dicots and monocots have evolved with a large preexisting repertoire of P-type ATPases. Both Arabidopsis and rice have representative members in all five major subfamilies of P-type ATPases: heavy-metal ATPases (P(1B)), Ca(2)(+)-ATPases (endoplasmic reticulum-type Ca(2)(+)-ATPase and autoinhibited Ca(2)(+)-ATPase, P(2A) and P(2B)), H(+)-ATPases (autoinhibited H(+)-ATPase, P(3A)), putative aminophospholipid ATPases (ALA, P(4)), and a branch with unknown specificity (P(5)). The close pairing of similar isoforms in rice and Arabidopsis suggests potential orthologous relationships for all 43 rice P-type ATPases. A phylogenetic comparison of protein sequences and intron positions indicates that the common angiosperm ancestor had at least 23 P-type ATPases. Although little is known about unique and common features of related pumps, clear differences between some members of the calcium pumps indicate that evolutionarily conserved clusters may distinguish pumps with either different subcellular locations or biochemical functions.